Increased compensatory kidney workload results in cellular damage in a short time porcine model of mixed acidemia - Is acidemia a ‘first hit’ in acute kidney injury? - Ruß, Martin; Kirschfink, Michael (PLOS ONE, 2019)
Acute kidney injury (AKI) corrupts the outcome of about 50% of all critically ill patients. We investigated the possible contribution of the pathology acidemia on the development of AKI. Pigs were exposed to acidemia, acidemia plus hypoxemia or a normal acid-base balance in an experimental setup, which included mechanical ventilation and renal replacement therapy to facilitate biotrauma caused by extracorporeal therapies. Interestingly, extensive histomorphological changes like a tubular loss of cell barriers occurred in the kidneys after just 5 hours exposure to acidemia. The additional exposure to hypoxemia aggravated these findings. These ‘early’ microscopic pathologies opposed intra vitam data of kidney function. They did not mirror cellular or systemic patterns of proinflammatory molecules (like TNF-α or IL 18) nor were they detectable by new, sensitive markers of AKI like Neutrophil gelatinase-associated lipocalin. Instead, the data suggest that the increased renal proton excretion during acidemia could be an ‘early’ first hit in the multifactorial pathogenesis of AKI.
Gesehen am 22.10.2019